Decision support framework for evaluating the operational environment of forest bioenergy production and use: Case of four European countries. (15th September 2016) - Pezdevšek Malovrh, Špela; Kurttila, Mikko; Hujala, Teppo; Kärkkäinen, Leena; Leban, Vasja; Lindstad, Berit H.; Peters, Dörte Marie; Rhodius, Regina; Solberg, Birger; Wirth, Kristina; Zadnik Stirn, Lidija; Krč, Janez
Abstract: Complex policy-making situations around bioenergy production and use require examination of the operational environment of the society and a participatory approach. This paper presents and demonstrates a three-phase decision-making framework for analysing the operational environment of strategies related to increased forest bioenergy targets. The framework is based on SWOT (strengths, weaknesses, opportunities and threats) analysis and the Simple Multi-Attribute Rating Technique (SMART). Stakeholders of four case countries (Finland, Germany, Norway and Slovenia) defined the factors that affect the operational environments, classified in four pre-set categories (Forest Characteristics and Management, Policy Framework, Technology and Science, and Consumers and Society). The stakeholders participated in weighting of SWOT items for two future scenarios with SMART technique. The first scenario reflected the current 2020 targets (the Business-as-Usual scenario), and the second scenario contained a further increase in the targets (the Increase scenario). This framework can be applied to various problems of environmental management and also to other fields where public decision-making is combined with stakeholders' engagement. The case results show that the greatest differences between the scenarios appear in Germany, indicating a notably negative outlook for the Increase scenario, while the smallest differences were found in Finland. Policy Framework was a highly rated category across the countries, mainly with respect to weaknesses and threats. Intensified forest bioenergy harvesting and utilization has potentially wide country-specific impacts which need to be anticipated and considered in national policies and public dialogue. Highlights: Policy-making situations around bioenergy require studying the operational environment. A three-phase framework for analysing the operational environment is developed. SWOT analysis is combined with SMART in the framework. The framework enables inclusion of various stakeholders and different scenarios. Shortcomings in political framework for bioenergy production and utilization exist.